The Homo Economicus as a Prototype of a Psychopath? A Conceptual Analysis and Implications for Business Research and Teaching - Florian Fuchs; Volker Lingnau (Journal of Business Ethics, 2024)
Since the beginning of business research and teaching, the basic assumptions of the discipline have been intensely debated. One of these basic assumptions concerns the behavioral aspects of human beings, which are traditionally represented in the construct of homo economicus. These assumptions have been increasingly challenged in light of findings from social, ethnological, psychological, and ethical research. Some publications from an integrative perspective have suggested that homo economicus embodies to a high degree dark character traits, particularly related to the construct of psychopathy, representing individuals who are extremely self-centered and ruthless, without feelings of remorse or compassion. While a growing body of research notes such a similarity on a more or less anecdotal basis, this article aims to explore this connection from a more rigorous perspective, bridging insights from psychological, economic, and business research to better understand the potentially dark traits of homo economicus. The analysis shows that homo economicus is not simply some kind of psychopath, but specifically a so-called subclinical or Factor 1 psychopath, who is also referred to as a “corporate psychopath” in business research. With such an analysis, the paper adds an additional perspective and a deeper psychological level of understanding as to why homo economicus is often controversially debated. Based on these insights, several implications for academic research and teaching are discussed and reflected upon in light of an ethics of virtue and care.
Keywords: 300; Homo economicus; Dark traits; Psychopathy